Identitas Ganda Gen Z di Media Sosial dalam Perspektif Islam - Moh Sudais (UIN Sunan Ampel Surabaya, 2026)
This study aims to analyze Generation Z users who maintain two Instagram accounts and construct dual identities on social media platforms. The research employs a qualitative method with a phenomenological approach. The findings indicate that the first account functions as a public space for self-presentation, where users construct an idealized image and manage social expectations. In contrast, the second account serves as a private sphere that allows greater freedom of expression, emotional sharing, and more authentic self-disclosure without the pressure of external judgment. Drawing on Self-Disclosure Theory and the dramaturgical perspective of Erving Goffman, the analysis demonstrates that Generation Z actively adjusts their identities according to different audiences. From an Islamic perspective, this practice aligns with the principles of safeguarding personal dignity, honesty, and privacy ethics, provided that the use of both accounts does not involve shameful content, reprehensible conduct, or moral violations. This study concludes that the digital dual identity constructed by Generation Z represents a strategy of self-management aimed at balancing the desire to appear ideal with the aspiration to remain authentic. It may therefore be understood as a form of communication ethics that remains consistent with Islamic values.